Professional Teachers’ Self-Assessment on Technological Pedagogical Content Knowledge (TPACK) in English Language Teaching - Rahmiyatus Shalihah; Iis Sujarwati (Universitas Islam Negeri Palopo, 2026)
The research used a descriptive survey design to offer an assessment in order to find out teachers’ perspective about TPACK implementation in English Language Teaching classroom. A total of 32 professional English teachers took part in this study by completing a TPACK survey questionnaire. Mean and standard deviation were used to analyze the qualitative data. The result showed that TPACK understanding of in-service professional English teachers is in the moderate level. Meanwhile, the technological and pedagogical integration result that the respondents showed satisfied level of competency. In general, comparative result in the three areas of ICT integration found that the ELT teachers are relatively higher.